INTEGRATION OF LARGE‐SCALE HEAT PUMPS IN THE DISTRICT HEATING SYSTEM OF SKOPJE - SHesho, Igor; Tashevski, Done; Filkoski, Risto; Monika Uler-Zefikj (University of Banja Luka, Faculty of Mechanical Engineering, 2021)
In the residential sector in EU countries space heating and domestic hot water system participate with more the 80% in the final energy consumption. Cost‐effective and energy efficient option for residential and commercial buildings is DHC which is currently dominated by fossil fuels, such as coal and gas. Upgrading existing systems with integrating renewable technologies can lead to significant benefits regarding climate change mitigation, energy security and human health. The main aim of this paper is analyzing the possibilities for integrating heat pump together with thermal storage in the district heating system in Skopje, R. North Macedonia, considering current network system, growing population, climate conditions and pollution issue. Different scenarios will be analyzed by changing the COP of the heat pump in order to get an overview of the most feasible option taking into consideration the heat production, electricity consumption and payback period. The energy model is developed and analyzed for the part operated by Balkan Energy Group. It tends to provide insight of the benefits provided by the system upgrade and cost analysis for installation, operation and maintenance of the equipment.
Keywords: district heating; heat pump; renewable energy